Interplanetary Scintillation Observations of Stream Interaction Regions in the Solar Wind - Bisi, M. M.; Fallows, R. A.; Breen, A. R.; O’Neill, I. J. (Solar Physics, 2010)
We present a summary of results from ten years of interplanetary scintillation (IPS) observations of stream interaction regions (SIRs) in the solar wind. Previous studies had shown that SIRs were characterized by intermediate-velocity solar wind and – in the case of compressive interactions – higher levels of scintillation. In this study we considered all cases of intermediate velocities in IPS observations from the European Incoherent SCATter (EISCAT) radar facility made at low- and mid-heliographic latitudes between 1994 and 2003. After dismissing intermediate-velocity observations which were associated with solar-wind transients (such as coronal mass ejections) we found that the remaining cases of intermediate velocities lay above coronal structures where stream interaction would be expected. An improved ballistic mapping method (compared to that used in earlier EISCAT studies of interaction regions) was used to identify the regions of raypath in IPS observations which might be expected to include interaction regions and to project these regions out to the distances of in-situ observations. The early stages of developing compression regions, consistent with their development on the leading edges of compressive stream interaction regions, were clearly detected as close to the Sun as 30 R ⊙, and further ballistic projection out to the distances of in-situ observations clearly associated these developing structures with density and velocity features characteristic of developed interaction regions in in-situ data in the cases when such data were available. The same approach was applied to study non-compressive interaction regions (shear layers) between solar-wind streams of different velocities where the stream interface lay at near-constant latitude and the results compared with those from compressive interaction regions. The results confirm that intermediate velocities seen in IPS observations above stream boundaries may arise from either detection of intermediate-velocity flow in compression regions, or from non-compressive shear layers. The variation in velocity about the mean determined from IPS measurements (representing the spread in velocity across that part of the raypath associated with the interaction region in the analysis) was comparable in compressive and non-compressive regions – a potentially interesting result which may contain important information on the geometry of developing SIRs. It is clear from these results that compressive and non-compressive interaction regions belong to the same class of stream – stream interaction, with the dominant mode determined by the latitudinal gradient of the stream interface. Finally, we discuss the results from this survey in the light of new data from the Heliospheric Imagers (HI) on the Solar TErrestrial RElations Observatory (STEREO) spacecraft and other instruments, and suggest possible directions for further work.